E-Mail Management in the Canadian Government: Overview of the Practices from a Records Management Perspective - Zwarich, Natasha; G. Park, Eun (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study explores the current e-mail management practices from the records management perspective in the Canadian Government. The research specifically focuses on the implementation of the e-mail management principles in government agencies in order to create, receive, maintain, preserve and provide access to e-mail messages. Cette étude explore les pratiques habituelles de gestion de courriels à partir de la perspective archivistique dans le milieu gouvernemental canadien. Cette recherche s’articule spécifiquement sur l’implantation des principes de gestion des courriels dans les agences gouvernementales de manière à créer, recevoir, gérer, préserver et offrir un accès aux messages courriels.